Syntheses, structures and properties of nickel(II) and manganese(II) coordination polymers based on V-shaped bis-imidazole and aromatic carboxylate ligands. (5th September 2016) - Lv, Lu-Lu; Zhang, Li-Jun; Zhao, Hong; Wu, Ben-Lai
Graphical abstract: A serial of Ni(II) and Mn(II) coordination polymers based on V-shaped mixed ligands bis-imidazole and aromatic carboxylic acids were solvothermally synthesized and fully characterized. Intriguingly, sorted-recognition and hierarchical assembly between Ni(II) and mixed ligands result in novel nanotubes. Abstract: Using V-shaped mixed ligands bis-imidazole and aromatic carboxylic acids, five new coordination polymers namely, [Ni(B-im)(Br-a)Cl]·H2 O n (1 ), [Ni(B-im)(I-a)(H2 O)2 ]·0.5H2 O n (2 ), [Ni(B-im)(I-a)(H2 O)2 ] n (3 ), [Ni(B-im)(M-a)(H2 O)2 ] n (4 ) and [Mn2 (B-im)2 (I-a)2 ]·2H2 O n (5 ) [B-im = 1, 1′-(5-methyl-1, 3-phenylene)bis(1H-imidazole), Br-a = 5-bromonicotinic acid, I-a = isophthalic acid and M-a = 5-methylisophthalic acid] were solvothermally synthesized and fully characterized by IR spectra, element analyses, X-ray powder and single-crystal diffractions, and thermogravimetric analyses. Complexes1 and2 feature polymeric macrocyclic chain structures containing interesting nanotubular channels, which are constructed by bridging 30-membered macrocyclic [Ni3 (B-im)3 ] subunits with Br-a ligands and by bridging folded 20-membered macrocyclic [Ni2 (B-im)2 ] subunits with I-a ligands, respectively. Isomorphic complexes3 and4 represent double-chain structures containing folded 18-membered macrocyclic [Ni2 (B-im)(I-a)] subunits and [Ni2 (B-im)(M-a)] subunits, respectively. Complex5 is a 2D porous coordination polymer containing novel chiral four-stranded Mn(II) chains consisting of two (B-im)-bridged aspiral chiral chains and two (I-a)-bridged heterochiral coaxial 21 -helical chains. The results of thermal gravimetric analyses suggest that the dehydrated frameworks of1 –5 are stable up to 320 °C. Additionally, the magnetism of complexes3 and5 were also investigated.